Does a Long-Run Relationship Exist between Trade Openness and Carbon Dioxide Emissions in Sri Lanka? - Maheswaranathan, Sarojini; Bhavan, Thangamani (Asian Development Policy Review, 2022)
In recent years, the process of globalization has provided a great deal of support to international trade, which has led to the increase in global trade volume. However, as far as the negative characteristics of international trade flows are concerned, the extensive production and trade needed to meet global demands have led to higher energy consumption and higher carbon dioxide (CO2) emissions. Sri Lanka has been trading since 1977, so the objective of this study is to investigate the existence of the relationship between trade and carbon dioxide emissions in Sri Lanka. Using annual time series data running from 1980 to 2014, this study employs Johansen’s cointegration method for econometric analysis. The findings of the study derived from the analysis revealed that the intended variables are likely to move together in the long run. The study suggests that reprocessing emissions, pollution prevention actions, and the introduction of low carbon technology in trade can mitigate carbon dioxide emissions.